Migracja aury lub jak badać oryginał poprzez jego faksymile - Latour, Bruno; Lowe, Adam; Lipiński, Filip (Artium Quaestiones, 2022)
The text offers enlightening reflections on issues concerning reproductions of works of art, the status of an original and a copy, the problem of conservation, and the role of digital photography. Latour and Lowe raise the contentious issue of how good and bad reproductions can affect the original, participate in what they call “the migration of the aura”. This is primarily a case study of a production, presentation, reception and the meaning of a facsimile of a Veronese work, Nozze di Cana at its original location, San Giorgio in Venice. The second part of the text (the appendix) is a meticulous, technical description of the stages of production of the picture by Lowe.